Silencing LINC00294 Restores Mitochondrial Function and Inhibits Apoptosis of Glioma Cells under Hypoxia via the miR-21-5p/CASKIN1/cAMP Axis - Xiaogang Dong (Hindawi Limited, 2021)
Glioma is a type of malignant intracranial tumor. Extensive research has identified the participation of long noncoding RNAs (lncRNAs) in glioma progression. This study investigated the mechanism of LINC00294 in mitochondrial function and glioma cell apoptosis. Glioma miRNA and mRNA microarray datasets were obtained, and differentially expressed lncRNAs in glioma were screened through various databases. The LINC00294 expression in glioma patients and glioma cells was detected. Glioma cells were treated under hypoxic conditions and transfected with LINC00294 silencing. The apoptosis and mitochondrial function of glioma cells were measured. The expressions of and relations among miR-21-5p, CASKIN1, and cAMP in glioma cells were analyzed. Under hypoxic conditions and LINC00294 silencing, the apoptosis and mitochondrial function of glioma cells were detected after inhibiting miR-21-5p or overexpressing CASKIN1. Our results indicated that LINC00294 was downregulated in glioma. LINC00294 silencing inhibited glioma cell apoptosis under hypoxia. LINC00294 silencing reversed the inhibition of hypoxia on mitochondrial function under hypoxia. LINC00294 promoted the CASKIN1 expression by sponging miR-21-5p and activated the cAMP pathway. Inhibition of miR-21-5p or overexpression of CASKIN1 annulled the effects of LINC00294 silencing on mitochondrial function and glioma cell apoptosis under hypoxia. In conclusion, LINC00294 elevated the CASKIN1 expression by sponging miR-21-5p and activating the cAMP signaling pathway, thus inhibiting mitochondrial function and facilitating glioma cell apoptosis.